An Overview of Topics on Accreditation: A Beginning. (September 2017) - Dassa, Lori; Ridener, Barbara; Sampson, Greg
Reflecting on the very nature of accreditation—and its enormous influence on the work of the academy—is an important activity. We propose that the manuscripts that were selected for publication encompass three major themes. This editorial summarizes those themes and provides some additional perspectives from us, as the editors of the journal.